2016
DOI: 10.1590/s0100-204x2016001000006
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Nile tilapia strains and their hybrids farmed in Brazil using microsatellite markers

Abstract: -The objective of this work was to evaluate a Bayesian model-based clustering method to identify the strains of Nile tilapia (Oreochromis niloticus) individuals from fish farms in Southern Brazil. Assignment methods using nine microsatellite loci were applied to differentiate individuals of five reference strains (GIFT, GST, Nilótica, Chitralada, and Saint Peter) and to identify individuals of unknown strains from fish farms near the Itaipu reservoir and in the Uruguay River basin. The procedure assigned the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
2
3
3
Order By: Relevance
“…According to the obtained estimate of He, both the silver-YY and the Thai strains (Chitralada-N, Chitralada-E, BIG NIN, and GIFT) had higher genetic variation in comparison with the Ugandan strains (Ruvu Farm-R, CHIFIVE-C, and Muleba-M). This observation is in agreement with findings of previous studies which compared improved strains with local farmed strains by using microsatellite markers (Romana-Eguia et al 2004;Baggio et al 2016). Hatchery practices and genetic management of fish stocks constitute key factors affecting the genetic diversity and long-term sustainability of the breeding populations.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…According to the obtained estimate of He, both the silver-YY and the Thai strains (Chitralada-N, Chitralada-E, BIG NIN, and GIFT) had higher genetic variation in comparison with the Ugandan strains (Ruvu Farm-R, CHIFIVE-C, and Muleba-M). This observation is in agreement with findings of previous studies which compared improved strains with local farmed strains by using microsatellite markers (Romana-Eguia et al 2004;Baggio et al 2016). Hatchery practices and genetic management of fish stocks constitute key factors affecting the genetic diversity and long-term sustainability of the breeding populations.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, the overall level of heterozygosity observed in our analysis is lower compared with prior tilapia studies (Fuerst et al 2000;Bhassu et al 2004;Hassanien and Gilbey 2005;Briñez et al 2011;Baggio et al 2016;Silva 2015). However, since the aforementioned studies utilized microsatellites, a direct comparison of heterozygosity magnitude may not be appropriate.…”
Section: Discussioncontrasting
confidence: 86%
“…The selection process applied in the Epagri brood stock over the last five years may explain this lower number of alleles. However, other studies with GIFT tilapia in Brazil, using a smaller number of animals and markers, showed a mean number of alleles per loci between 4.2 and 6.1 (Rodriguez-Rodriguez et al, 2013;Baggio, Orélis-Ribeiro, & Boeger, 2016;Dias, Freitas, Arranz, Villanova, & Hilsdorf, 2016), which is lower than that found in this study. Regarding the Hardy-Weinberg equilibrium, it was observed that the number of loci per stock ranged from four to ten for populations S1 and S6, respectively.…”
contrasting
confidence: 82%
“…Despite the deliberate production of interspecific and intergeneric freshwater hybrids for genetic improvement (Hashimoto et al., ), no laws currently regulate this practice in Brazil (Hashimoto et al., ; Suplicy, ). Large proportions of genetic introgression in natural populations have already been observed in studies of wild catfish populations of Pseudoplatystoma corruscans and Pseudoplatystoma reticulatum in the Paraná and Paraguay River Basins, and this introgression is the result of hybrid and F1 hybrids escaping from aquaculture farms (Baggio, Orélis‐Ribeiro & Boeger, ; Do Prado et al., ).…”
Section: Discussionmentioning
confidence: 86%